Serum Levels of Interleukin-2 and Interleukin-6 among Helicobacter Pylori Positive Patients in Relation to Prognosis of Gastro-duodenal Disease - Methaq M. Neamah AL-Hilfi; Khairallah A.S Mohammed; Naael H. Ali; Ali Dawood AL-Hilfi (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Helicobacter pylori is the most widespread pathogenic associated with gastro-duodenal Disease. Interleukin 2 and interleukin 6 are the main cytokines involved in host immune response to H.pylori infection. The aim of the present study are to assess the serum level of IL-6 and IL–2 in H.pylori infected patients and to study their association with gastric endoscopy findings. Methods: One hundred and seven suspected patients and 19 healthy were recruited. The confirmed positivity of H.pylori detection was based on a rapid urease test (R.U.T) and stool antigen test. Serum concentrations of IL-2 and IL-6 were measuring by ELISA. Results: Seventy-five (70%) patients were positive for H.pylori. Both interleukins were found at higher levels in patients than in healthy (p- value <0.05). Interestingly, the level of IL-2 was lower in patients infected with H.pylori (43.40 pg/ml) than those who were not infected (85.2 pg/ml), while the level of IL-6 was higher in patients infected with H.pylori (117 pg/ml) than those not infected (40 pg/ml), p-value <0.05. Furthermore, the increasing levels of both interleukins were correlated with disease progress.